Avaliação da influência da água e enxofre no controle microbiológico em combustíveis diesel Bx utilizando radiação ultravioleta - Polinarski, Marcos Antonio (2020)
The presence of microorganisms in diesel oil, biodiesel and their blends, is an issue that has been well documented in the literature, especially due to the negative effects that it tends to cause, for example, the sludge formation, clogging of filters and valves and storage tanks corrosion. With the gradual increase in the levels of biodiesel to commercial diesel, the precautions during fuel storage should be greater, since this biofuel has a hygroscopic character, which facilitates contamination due to the water absorption capacity. One of the ways to avoid microbiological contamination is the application of techniques such as periodic cleaning of storage tanks or the use of biocides. However, their use may be associated with changes in the fuel physicochemical parameters. The aim of this work was to evaluate the presence of microorganisms in diesel fuel B11 and B20 with variations in the sulfur (10 ppm and 500 ppm) and water (without addition, 2500 ppm and 10000 ppm) content, and to propose the use of ultraviolet radiation as alternative to microbial control and to verify if the UV use promotes changes in the fuel physical-chemical characteristics. The fuel samples were stored for 10 days, where the presence of microorganisms was monitored from the absorbance reading. After storage, the fuels were exposed to ultraviolet radiation for 360 minutes, and the microorganisms presence was monitored every 45 minutes. Water content, viscosity, density and oxidative stability were evaluated at the beginning and end of the treatment. After the treatment the microorganisms presence was followed during 30 days. The results showed that during simulated storage, fuels with water addition were the most susceptible microorganisms growth, while fuels without alteration the most significant changes were related to a higher sulfur content. The ultraviolet radiation treatment showed efficiency higher than 90% for 2 of the 12 samples analyzed, while only 4 samples had an efficiency lower than 50% in the microorganisms presence reduction. Regarding the physical-chemical parameters, it was found that the use of ultraviolet radiation promoted statistically significant changes but did not change the final quality of the fuel. The UV treatment proved to be stable for up to 10 days after its application. The results have showed the potential of ultraviolet radiation as a method of microbial control and reduction of sulfur levels does not increase microbial contamination in the fuel, with the presence of water being the main reason for contamination.